2007
DOI: 10.1111/j.1744-7429.2007.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Exotic Guavas are Foci of Forest Regeneration in Kenyan Farmland

Abstract: Fruiting trees in degraded areas are attractive for frugivorous birds and may become centers of regeneration. However, a number of tree species in degraded areas are exotic species. Thus, the question arises whether these exotic species can also act as foci for forest regeneration. In the farmland adjacent to Kakamega Forest, Kenya, we investigated the frugivore assemblage in, and seed rain and seedling establishment under, 29 fruiting exotic guava trees (Psidium guajava) at different distances to the forest. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 50 publications
1
53
2
1
Order By: Relevance
“…In the short-term, foraging on C. hirta is beneficial for the restoration project since it provides fruits year-round [Wester and Wood, 1977] and draws lemurs into the parcels, allowing dispersal of a diversity of forest seed species. Successful restoration programs in the tropics use remnant or man-made perches [Janzen, 1988;Holl et al, 2000;Shiels and Walker, 2003] or planted food trees [Toh et al, 1999;Berens et al, 2008] to lure avian and mammalian dispersal agents into non-forest landscapes, but studies have also shown that early successional shrubs are important for the initiation of forest regeneration [Nepstad et al, 1991;Vieira et al, 1994;Zahawi and Augspurger, 1999;Duncan and Chapman, 2002]. In the long term, the structure of the forest at MNP might be affected by V. rubra dispersing C. hirta seeds into the mature forest, since this species can thrive under an open or a closed canopy [Wester and Wood, 1977].…”
Section: Forest Restorationmentioning
confidence: 99%
“…In the short-term, foraging on C. hirta is beneficial for the restoration project since it provides fruits year-round [Wester and Wood, 1977] and draws lemurs into the parcels, allowing dispersal of a diversity of forest seed species. Successful restoration programs in the tropics use remnant or man-made perches [Janzen, 1988;Holl et al, 2000;Shiels and Walker, 2003] or planted food trees [Toh et al, 1999;Berens et al, 2008] to lure avian and mammalian dispersal agents into non-forest landscapes, but studies have also shown that early successional shrubs are important for the initiation of forest regeneration [Nepstad et al, 1991;Vieira et al, 1994;Zahawi and Augspurger, 1999;Duncan and Chapman, 2002]. In the long term, the structure of the forest at MNP might be affected by V. rubra dispersing C. hirta seeds into the mature forest, since this species can thrive under an open or a closed canopy [Wester and Wood, 1977].…”
Section: Forest Restorationmentioning
confidence: 99%
“…Commonly known as guava tree, Psidium guajava L. is a Myrtaceae originally from Central America from Southern Mexico to Northern South America (Morton, 1987). The species has been registered as invasive in pasture (Somarriba, 1985) and as an important pioneer species in the process of forest recovery on abandoned pasture (Aide et al, 2000;Berens, 2008). The success of P. guajava in occupying pasture is often attributed to its regrowth ability and to the dispersion of its seeds by birds and cattle (Berens, 2008, Somarriba, 1985.…”
Section: Introductionmentioning
confidence: 99%
“…The species has been registered as invasive in pasture (Somarriba, 1985) and as an important pioneer species in the process of forest recovery on abandoned pasture (Aide et al, 2000;Berens, 2008). The success of P. guajava in occupying pasture is often attributed to its regrowth ability and to the dispersion of its seeds by birds and cattle (Berens, 2008, Somarriba, 1985. The P. guajava has been registered as an invasive species of secondary forests on abandoned pasture in the Upper Paraná River Floodplain (Campos and Dickinson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Many cases of this phenomenon have been described among native species (Vieira et al 1994, Clark et al 2004, Carlo 2005, Carlo & Aukema 2005, García et al 2007, Von Zeipel & Eriksson 2007, Carlo & Tewksbury 2014 and some also among introduced invasive species (Tecco et al 2006, 2007, White & Vivian-Smith 2011. Moreover, facilitation of native species recruitment by non-native fleshy-fruiting trees has been reported (Neilan et al 2006, Foster & Robinson 2007, Bernes et al 2008. Surprisingly, seed dispersal facilitation of exotic species by native species is either less common or has not been properly documented so far.…”
Section: Invasion Of Rubus Praecox (Rosaceae) Is Promoted By the Natimentioning
confidence: 99%